PIP5k1β controls bone homeostasis through modulating both osteoclast and osteoblast differentiation. (16th April 2019) - Zhao, Xiaoying; Cui, Penglei; Hu, Guoli; Wang, Chuandong; Jiang, Lei; Zhao, Jingyu; Xu, Jiake; Zhang, Xiaoling
Abstract: PIP5k1β is crucial to the generation of phosphotidylinosotol (4, 5)P2 . PIP5k1β participates in numerous cellular activities, such as B cell and platelet activation, cell phagocytosis and endocytosis, cell apoptosis, and cytoskeletal organization. In the present work, we aimed to examine the function of PIP5k1β in osteoclastogenesis and osteogenesis to provide promising strategies for osteoporosis prevention and treatment. We discovered that PIP5k1β deletion in mice resulted in obvious bone loss and that PIP5k1β was highly expressed during both osteoclast and osteoblast differentiation. Deletion of the gene was found to enhance the proliferation and migration of bone marrow-derived macrophage-like cells to promote osteoclast differentiation. PIP5k1β −/− osteoclasts exhibited normal cytoskeleton architecture but stronger resorption activity. PIP5k1β deficiency also promoted activation of mitogen-activated kinase and Akt signaling, enhanced TRAF6 and c-Fos expression, facilitated the expression and nuclear translocation of NFATC1, and upregulated Grb2 expression, thereby accelerating osteoclast differentiation and function. Finally, PIP5k1β enhanced osteoblast differentiation by upregulating master gene expression through triggering smad1/5/8 signaling. Therefore, PIP5k1β modulates bone homeostasis and remodeling.